Culture as digital discipline: Gender exclusion and power relations among generation Z - Reni Alfiyah; A. Hardiyanti; Alwi Usra Usman (Jurnal Anifa: Studi Gender dan Anak, 2026)
The rapid expansion of digital spaces has transformed Generation Z’s social interactions, while also intensifying gender-based exclusion through cancel culture. Despite growing attention to cancel culture, its role as a mechanism of digital discipline in reproducing gendered power relations remains under explored. This study examines how cancel culture functions as a mechanism of gender exclusion and digital control among Generation Z. A critical qualitative case study was conducted using social media observations, digital content analysis, and in-depth interviews with Generation Z university students at Universitas Negeri Makassar. The data were analyzed using Critical Discourse Analysis. The findings reveal that cancel culture operates not only as a form of public criticism but also as a mechanism of digital discipline, surveillance, and symbolic exclusion that disproportionately targets women and marginalized gender groups. These practices reinforce gender performativity and reproduce unequal power relations in digital spaces. This study contributes to digital sociology by demonstrating that cancel culture functions as a gendered mechanism of digital governance and highlights the importance of critical digital literacy in fostering more inclusive and equitable digital environments.